Diagnostic Accuracy of Combination of Total Leukocyte Count and CRP for Diagnosis of Early Onset Neonatal Sepsis using Blood Culture as Gold Standard - Shahid, Saim; Liaqat, Samra; Umbreen , Hina; Ayub , Muhammad Muaz (Indus Journal of Bioscience Research, 2025)
Objective: Using blood culture as the gold standard, ascertain the diagnostic accuracy of the total leukocyte count and CRP combination for the diagnosis of early-onset newborn sepsis. Study design and Settings: A cross-sectional validation study was conducted at the department of Pediatrics, Allied Hospital 1, Faisalabad, for the duration of six months, from April 2024 to September 2024. Materials and Procedures: Participants in this study included 225 patients who met the selection criteria. Following aseptic procedures, a sterile 5-milliliter syringe was used to draw 5 milliliters of intravenous blood, which was then sent to the hospital’s pathology lab for pathologist investigation. Blood was cultured for 24 hours at 37°C in a bottle of brain-heart infusion broth. Blood and MacConkey agar were used for the subculture, which was then aerobically incubated for the entire night at 37°C. In compliance with predetermined standards, organisms were identified. According to operational guidelines, a positive blood culture was regarded as the gold standard for detecting early-onset sepsis. C-reactive protein levels and total leukocyte count were combined to determine early-onset newborn sepsis. Results: Using blood culture results as the gold standard, the combined TLC and CRP for the diagnosis of early onset neonatal sepsis showed sensitivity of 92.04%, specificity 94.64%, PPV 94.55%, NPV 92.18%, and accuracy of 93.33%, respectively. Conclusion: The combination of total leukocyte count and CRP serves as an effective measure to avoid antibiotic abuse, hence inhibiting the colonization of drug-resistant microbiota in newborns.